2014
DOI: 10.1007/s00259-014-2708-8
|View full text |Cite
|
Sign up to set email alerts
|

PET imaging reveals brain functional changes in internet gaming disorder

Abstract: For the first time, we report the evidence that D2 receptor level is significantly associated with glucose metabolism in the same individuals with internet gaming disorder, which indicates that D2/5-HT2A receptor-mediated dysregulation of the orbitofrontal cortex could underlie a mechanism for loss of control and compulsive behavior in internet gaming disorder subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 43 publications
4
65
1
2
Order By: Relevance
“…Recently, "behavioral addiction" has also been proposed, but is beyond this review and has been described in detail elsewhere [10][11][12][13][14][15][16][17][18] .…”
Section: Drug Addictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, "behavioral addiction" has also been proposed, but is beyond this review and has been described in detail elsewhere [10][11][12][13][14][15][16][17][18] .…”
Section: Drug Addictionmentioning
confidence: 99%
“…From the 17th century, addiction has been used to refer to psychoactive substances (e.g. alcohol, tobacco, heroin) which cross the blood-brain barrier, temporarily altering the chemical milieu of the brain [8] .Currently, addiction is identified as continued involvement with a drug, despite the negative consequences associated with it -such as compulsive drug seeking and taking, loss of control over drug-taking, or emergence of a negative emotional state (e.g., dysphoria, anxiety, irritability) -when access to the drug is prevented or terminated [9] .Recently, "behavioral addiction" has also been proposed, but is beyond this review and has been described in detail elsewhere [10][11][12][13][14][15][16][17][18] .The neuronal basis of addiction has been guided by the premise that the motivation of an addict to take drugs results from the desire to experience the hedonic (i.e., rewarding) effects or from the desire to avoid the anhedonia and aversive consequences of withdrawal [19] . There are mounting studies suggesting that the rewarding properties of addictive drugs depend on their ability to provoke DA release in the brain [20][21][22] .…”
mentioning
confidence: 99%
“…In the study by Tian et al [1], individuals with IGD showed a significant decrease in glucose metabolism in the prefrontal, temporal and limbic systems together with dysregulation of D2 receptors in the striatum, correlated with the number of years of overuse. Low levels of D2 receptors were significantly associated with decreased glucose metabolism in the orbitofrontal cortex, suggesting that D2/5-HT2A receptormediated dysregulation of the orbitofrontal cortex could be the underlying mechanism for loss of control and compulsive behaviour in IGD.…”
Section: The Old Times (About 30 Years Ago)mentioning
confidence: 96%
“…In this issue Tian et al [1] report that PET can be used to reveal brain functional changes in subjects with internet gaming disorder (IGD), using either N-methylspiperone ( 11 C-NMSP), to assess the availability of D2/5-HT2A receptors, or 18 Ffluoro-D-glucose ( 18 F-FDG). Twelve drug-naive men who met the criteria for IGD and 14 matched controls were studied under both resting and internet gaming task states, playing World of Warcraft, one of the most widely recognized "massively multiplayer online role-playing games" (MMORPG), which showed a compulsive behaviour in many people worldwide.…”
Section: The Old Times (About 30 Years Ago)mentioning
confidence: 99%
See 1 more Smart Citation